2007
DOI: 10.1016/j.jcrs.2007.06.056
|View full text |Cite
|
Sign up to set email alerts
|

Effect of square-edged intraocular lenses on neodymium:YAG laser capsulotomy rates in the United States

Abstract: After the introduction of square-edged IOLs, Nd:YAG laser capsulotomy rates decreased, but not by as much as predicted. The additional cost to the Medicare system was more than US $30 million higher than the model predicted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 49 publications
(50 reference statements)
0
14
0
Order By: Relevance
“…However, in spite of these improvements about 10% of patients still require a Nd:YAG laser capsulotomy within 2 years of surgery and these numbers continue to rise with greater post-surgical time (Vock et al, 2009). This places a strain on healthcare resources, medical time and the quality of a patient's life (Cleary et al, 2007). These problems are exacerbated in paediatric eyes, eyes with inflammation or with multifocal IOLs.…”
Section: Introductionmentioning
confidence: 99%
“…However, in spite of these improvements about 10% of patients still require a Nd:YAG laser capsulotomy within 2 years of surgery and these numbers continue to rise with greater post-surgical time (Vock et al, 2009). This places a strain on healthcare resources, medical time and the quality of a patient's life (Cleary et al, 2007). These problems are exacerbated in paediatric eyes, eyes with inflammation or with multifocal IOLs.…”
Section: Introductionmentioning
confidence: 99%
“…a sharp IOL optic edge [10]. Although the use of sharp-edged IOLs initially appeared to reduce the prevalence of PCO, recent reports have shown that the need for neodymium:YAG (Nd:YAG) laser capsulotomy is not as low as expected, but instead postponed, and other means than the IOL design have to beconsidered to prevent PCO [11-13]. Extended knowledge about patient-associated risk factors could lead to ways of developing new preventive strategies.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the introduction of sharp-edge optic IOL and the development of the modern phacoemulsification technique have resulted in reduced rates of PCO. (1)(2)(3) Standard treatment of the PCO is neodymium-doped yttrium aluminium garnet (Nd:YAG) laser capsulotomy. This procedure is effective but it has several complications such as postoperative intraocular pressure (IOP) elevation, IOL damage, inflammation, cystoid macular edema, and retinal detachment.…”
mentioning
confidence: 99%